Foundations of photonic crystal fibres - Zolla, Frédéric (World Scientific, 2005)
This book aims to provide expert guidance to researchers experienced in classical technology, as well as to those new to the field. A variety of perspectives on Photonic Crystal Fibres (PCFs) is presented together with a thorough treatment of the theoretical, physical and mathematical foundations of the optics of PCFs. The range of expertise of the authors is reflected in the depth of coverage, which will benefit those approaching the subject for a variety of reasons and from diverse backgrounds. The study of PCFs enables us to understand how best to optimize their applications in communicatio.